Main Character’s Personality in the Novel Adikku Pahlawanku by Fayanna Ailisha Davianny and Doa untuk Mama by Najla Nurdiany Putri - Salmah; Suyatno (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study describes the objectives of (1) physiological needs, (2) security needs, (3) love and belonging needs, (4) esteem needs, and (5) self-actualization needs of the main characters in the novels Adikku Pahlawanku by Fayanna Ailisha Daviany and Doa Untuk Mama by Najla Nurdiany Putri. The phenomena found in this study indicate that the two main characters, namely Tari and Aisyah, experience a layered process of fulfilling needs, starting from fulfilling basic needs such as food and health to higher psychological needs such as emotional support, appreciation, and self-development. In addition, this study found psychological tension in the form of economic anxiety, physical anxiety, and emotional conflict that affect the process of fulfilling the needs of the main characters, but in the end these needs can be fulfilled through the support of family and social environment. Data collection through the process of reduction, grouping, and interpretation of relevant quotes from both novels based on the categories of physiological needs, security, love and belonging, appreciation, and self-actualization in accordance with Maslow’s hierarchy of needs theory. The research findings show that both novels display the dynamics of human needs as a whole. Tari and Aisyah are depicted as child characters capable of building emotional resilience through warm family relationships. This research’s contribution lies in explaining how children’s literature, particularly the novel KKPK, can serve as a medium for understanding the psychological development of child characters and its relevance to the formation of readers’ characters. Furthermore, this research enriches the study of literary psychology by demonstrating that Maslow’s theory can be effectively applied to children’s literary texts as objects of scientific study.